2016
DOI: 10.1148/radiol.2015150673
|View full text |Cite
|
Sign up to set email alerts
|

Asymptomatic Progressive Multifocal Leukoencephalopathy Associated with Natalizumab: Diagnostic Precision with MR Imaging

Abstract: Recognition of the most predictive imaging features and comparison with previous MR imaging data may facilitate the detection of asymptomatic NTZ PML.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
34
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(34 citation statements)
references
References 21 publications
0
34
0
Order By: Relevance
“…In previous studies, punctiform T2/FLAIR hyperintense lesions in the vicinity of the main PML lesions, also described as ‘milky way appearance’ when being present in high numbers,22 showed to be common in symptomatic and asymptomatic natalizumab-associated PML 21 22 30 33. Punctiform T2 lesions are also seen further away from the main PML lesion, even in the hemisphere contralateral to the main PML lesion, and can have a perivascular distribution pattern suggestive of perivascular inflammation 22 26 30.…”
Section: Discussionmentioning
confidence: 92%
See 2 more Smart Citations
“…In previous studies, punctiform T2/FLAIR hyperintense lesions in the vicinity of the main PML lesions, also described as ‘milky way appearance’ when being present in high numbers,22 showed to be common in symptomatic and asymptomatic natalizumab-associated PML 21 22 30 33. Punctiform T2 lesions are also seen further away from the main PML lesion, even in the hemisphere contralateral to the main PML lesion, and can have a perivascular distribution pattern suggestive of perivascular inflammation 22 26 30.…”
Section: Discussionmentioning
confidence: 92%
“…Indeed, the recent study by Hodel et al 33 nicely showed that a subcortical lesion location, involving the U fibres, was predictive for asymptomatic natalizumab-associated PML. In contrast, a focal lesion appearance and lesions located in the periventricular white matter were strongly associated with new MS lesions instead of asymptomatic PML, which is not surprising since this type of lesion is one of the well-known stereotype MS lesions included in the MRI diagnostic criteria for MS 31.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…In addition, perilesional contrast enhancement around confluent PML-suspicious lesions suggestive of IRIS was detectable (Figure 2). Diffusion weighted MRI did not show intralesional hyperdiffusivity nor signs of restricted diffusion at the edge of the lesions (Figure 3); both of which are considered to be typical of PML [14]. …”
Section: Case Presentationmentioning
confidence: 99%
“…3,4 Awareness of these specific lesion patterns and the use of an adequate MR imaging protocol facilitate an earlier diagnosis of asymptomatic NTZ-PML, associated with a more favorable prognosis.…”
mentioning
confidence: 99%